The meaning construction of Chinese compounds : A cognitive semantic perspective / Leong Wen Xin - Leong, Wen Xin (2015)
The purpose of this study is an examination of the meaning construction of Chinese compounds from the perspective of cognitive semantics. Chinese compounds are a significant part of the Chinese language. However, the meanings of Chinese compounds are not all overtly expressed in their forms. Thus, Chinese compounds have received considerable attention over the years in studies from both cognitive and morphological perspectives. Cognitive studies typically use metaphor and metonymy to analyse the meaning construction of Chinese compounds, and their data are limited to compounds containing body-part terms and human organs. Morphological studies, on the other hand, tend to focus their attention on the structural relationship of the components of the compounds. The Conceptual Blending approach developed by Fauconnier and Turner (1998, 2002), demonstrating how two different component parts are combined to form a new compound, has mostly been applied to English compounds. Until now, no study has applied this approach to the analysis of Chinese compounds. This study applies Conceptual Blending on the Chinese compounds sourced from a Chinese short story. The short story is entitled 师傅越来越幽默Shīfu yuèláiyuè yōumò ‘Master, You’ll Do Anything for a Laugh’ by Mo Yan (2012). All disyllabic Chinese compounds selected from the short story are identified and classified according to Bloomfield’s (1957) semantic classification into endocentric and exocentric compounds. A partially-endocentric classification is introduced in this study to facilitate analysis. The two parts of data analysis are descriptive and theoretical. A descriptive approach is used to describe the characteristics of the endocentric, partially-endocentric, and exocentric compounds. Under the theoretical approach, Conceptual Blending is only applied to the partially-endocentric and exocentric compounds because the meaning constructions of these two types are not fully explicit. The Conceptual Blending approach, which involves a generic space, two input spaces, and a blended space, may show how emergent meaning is derived for the two types of compounds. The findings show that the inclusion of endocentric, partially-endocentric, and exocentric compounds has made the writing of the short story more earthly and interesting. An endocentric compound has a lexical head that specifies the class of the compound, and its meaning construction is direct and explicit. A partially-endocentric compound has a lexical head which is transparent in meaning while the non-head has implicit meanings. Exocentric compounds are not explicit in terms of meaning but may be interpreted metaphorically or with the help of one’s encyclopaedic knowledge. It is found that Chinese speakers make use of the nature of their human bodies when coining partially-endocentric and exocentric compounds. Thus, the conceptual structure of the Chinese compounds is largely embodied in that nature. It can be concluded that the meanings manifested in the Chinese compounds are inextricably linked with the way Chinese speakers experience the world, the nature and functions of their bodies, and their encyclopaedic knowledge about things in life.